2014
DOI: 10.1007/s00586-014-3387-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between laminoplasty opening angle and increased sagittal canal diameter and the prediction of spinal canal expansion following double-door cervical laminoplasty

Abstract: Purpose To clarify the relationship between laminoplasty opening angle (LOA) and the increase in sagittal canal diameter (SCD) in double-door cervical laminoplasty (DDCL) and to predict the increase in SCD using the resulting formula. Methods We analyzed 20 patients with multilevel cervical spondylotic myelopathy who underwent DDCL between September 2010 and January 2013. The pre-and post-operative parameters of the cervical spinal canal were measured by computed tomography. We deduced a formula describing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, they did not perform an analysis of SCA changes according to preoperative LA, which can affect SCA expansion in laminoplasty. The same group reported using a similar program in DDL and concluded that it was feasible for predicting SCA expansion 7) . They suggested that SCA expansion was proportional to the preoperative LA and OS but did not provide data regarding the differences between ODL and DDL according to preoperative LA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they did not perform an analysis of SCA changes according to preoperative LA, which can affect SCA expansion in laminoplasty. The same group reported using a similar program in DDL and concluded that it was feasible for predicting SCA expansion 7) . They suggested that SCA expansion was proportional to the preoperative LA and OS but did not provide data regarding the differences between ODL and DDL according to preoperative LA.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our clinical data, DDL resulted in more SCA expansion at every level, indicating that SCA expansion does not merely depend on the type of laminoplasty and that it instead depends on the length of the spacer, the OA, and the location of the hinge and lateral gutter ( Table 2). Few studies have been performed to predict SCA expansion using simulation modeling or computerized programs 6,7,19) . Wang et al 19) used a computer-simulated comparison to predict spinal canal expansion following cervical laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of the dural tube after cervical laminoplasty has been previously reported [1][2][3][4] . Post-laminectomy membrane was found to deteriorate during neurological recovery after a conventional laminectomy and therefore, was a reason for the invention of laminoplasty 1,5) .…”
Section: Introductionmentioning
confidence: 88%